An assessment of the policy gap in port selection of liner shipping companies. Issue 4 (21st April 2021) - Hsu, Wen-Kai; Huang, Show-Hui Sheree; Tseng, Wen-Jui; Li, Dong-Feng
ABSTRACT: This paper aims to assess the policy gap in port selection of liner shipping companies. Based on the operational features of liner shipping and relevant literature, the port selection factors (PSFs) of liner shipping companies are first investigated. An assessment model of the policy gap based on an improved ANP (Analytic Network Process) approach is then proposed to assess the perceived differences in PSFs between the shipping companies and port companies. As an empirical study, the liner shipping companies in Taiwan and the Taiwan International Port Company (TIPC) were carried out to validate the model. The results indicate the PSFs related to Cargo volume are more important than those related to Port charge . Moreover, currently, TIPC faces two significant gaps, including one negative gap, Labor disputes, and one positive gap, Numbers and frequency of trunk shipping . Based on the results, theoretical and managerial implications are discussed.